Correlation and Logical Consequences between Pancasila and the Perspective of Tradition - Iskandarsyah Siregar (Britain International for Academic Research (BIAR-Publisher), 2022)
The long road of economic and political modernisation of Democracy in Indonesia has transformed Indonesian society into an industrial community that has not empowered the people's economic sectors. The ups and downs of democratic politics remain far from the culture of deliberation mandated by Pancasila. The combination of development politics that has hit collective economic and cultural wisdom with political liberalisation in the past 15 years has negatively impacted Indonesian cultural identity. The following study seeks to reconstruct the local knowledge and political values of Indonesian ethnic groups and communities to demonstrate the potential of social capital to improve our democratic politics. The object of the study consists of two types: the first is ethnic groups, with a focus on Wajo and Minang, and the second is the communities of several urban parks in Java. The theoretical perspective used is the theory of consultative Democracy. From the point of view of political anthropology, this study is a case study in the context of qualitative research with qualitative-interpretive methods.